Remedial Boundary Work and Gatekeeper Centrality in a Virtual Entrepreneur Community - Santana, Jessica J. (Frontiers in Communication, 2022)
Virtual communities of practice invoke novel forms of boundary work that are newly visible via publicly recorded discourse and failure narratives. This boundary work has critical implications for occupational knowledge, membership, and stratification. Building on social exchange theorization of network gatekeeping, I test the assumption that centralized peers are more competitive gatekeepers, in that they react more negatively to remedial narratives. I test this theory using empirical data from a virtual entrepreneur community on Reddit. I find that a peer’s tenure in the community network is directly related to exclusive, competitive boundary work of remedial members. However, by looking beyond the network structure to the content of the tie, I find that exclusive boundary work is not as impactful as inclusive, collaborative boundary work in this open network setting. I build on relational cohesion and exchange commitment theory to explain how remedial practitioners circumvent central community gatekeepers through failure narratives that provoke empathy from peripheral peers who experience higher uncertainty than core peers. Understanding these dynamics is critical to promoting recovery from failure and vitality of the community of practice.